Antibacterial Efficacy of Chitosan Nanoparticle Based Intracanal Medicament Compared with Conventional Intracanal Medicament for Root Canal Disinfection - A Systematic Review - Manoj, Atluri; Ranjan, Manish; Singh, Sanyukta; C. Ragavendran, (Journal of Neonatal Surgery, 2025)
Background: Root canal disinfection is crucial for the success of endodontic treatment, with intracanal medicaments playing a significant role in eliminating microbial infections. Conventional medicaments such as calcium hydroxide and chlorhexidine are widely used, but their limitations have led to the exploration of novel formulations. Chitosan nanoparticles, due to their antimicrobial properties and biocompatibility, have emerged as promising alternatives. Objective: This systematic review aims to evaluate the antibacterial efficacy of chitosan nanoparticle-based intracanal medicaments in comparison to conventional intracanal medicaments for root canal disinfection. Methods: A comprehensive literature search was conducted in PubMed, SCOPUS, and Web of Science databases, following PRISMA guidelines. Studies assessing the antibacterial effectiveness of chitosan nanoparticle-based intracanal medicaments against Enterococcus faecalis and other endodontic pathogens were included. Data extraction and risk of bias assessment were performed independently by two reviewers. Results: Seven in vitro studies met the inclusion criteria. The reviewed studies utilized various formulations of chitosan nanoparticles, including combinations with calcium hydroxide, chlorhexidine, and propolis. Antimicrobial assessments were conducted using colony-forming unit (CFU) analysis, scanning electron microscopy (SEM), and spectrophotometry. Five studies demonstrated enhanced antibacterial efficacy with chitosan nanoparticle-based medicaments compared to conventional agents, while two studies showed comparable but not superior effects. Conclusion: Chitosan nanoparticle-based intracanal medicaments exhibit significant antibacterial potential and may serve as effective alternatives to conventional medicaments. Their ability to enhance antimicrobial activity and provide controlled drug release suggests promising clinical applications. However, further standardized in vivo studies are required to validate their efficacy and long-term benefits.